Does the @realDonaldTrump Really Matter to Financial Markets?. Issue 1 (4th December 2019) - Benton, Allyson L.; Philips, Andrew Q.
Abstract: Does the @realDonaldTrump really matter to financial markets? Research shows that new information about the likely future policy direction of government affects financial markets. In contrast, we argue that new information can also arise about the likely future government's resolve in following through with its policy goals, affecting financial markets as well. We test our argument using data on U.S. President Donald J. Trump's Mexico‐related policy tweets and the U.S. dollar/Mexican peso exchange rate. We find that Trump's Mexico‐related tweets raised Mexican peso volatility while his policy views were unknown as well as thereafter, as they signaled his resolve in carrying out his Mexico‐related agenda. By helping politicians disseminate policy information to voters, and since voters hold governments accountable for their policy performance, social media allows investors to gather information about the likely policy direction and policy resolve of government, especially those of newcomers whose direction and resolve are unknown.